Probability, Statistics and Random Processes - P. Kousalya (Chennai Dorling Kindersley (India) Pvt. Ltd.Pearson, 2013)
Description this book is designed to meet the requirements of studentsand is intended for beginners to help them understand the conceptsfrom the first principles. Spread across 16 chapters, it discussesthe theoretical aspects that have been refined and updated toreflect the current developments in the subjects. It expounds ontheoretical concepts that have immense practical applications,giving adequate proofs to establish significant theorems.
Keywords: Probabilities. Mathematical statistics